MANAGEMENT OF ECO-PESANTREN-BASED CRITICAL LAND DISASTER MITIGATION (CASE STUDY OF THE HIDAYATULLAH ISLAMIC BOARDING SCHOOL IN GUNUNG TEMBAK BALIKPAPAN KALIMANTAN) - Aulia, Rihlah Nur; Jasin, Fasial M; Irma, Asma (Unnes Science Education Journal, 2019)
This study aims to develop eco-pesantren-based critical land disaster mitigation management models. This study uses the theory of community-based disaster risk management). The method used is a qualitative research method by collecting data through field observations, interviews, documentation, and literature. This study concludes, first, the eco-pesantren-based critical land disaster mitigation management model, the fundamental environmental problems faced by Hidayatullah Islamic boarding school are as follows, namely: Threats of land damage, Forest damage, Threat of death of water sources. Second, management of critical land disaster mitigation carried out by the Hidayatullah pesantren, namely; the involvement of the pesantren academic community actively in solving environmental problems in the surrounding community of pesantren such as reforestation, by changing settlements in the form of wilderness and swamps to make the pesantren and surrounding areas green, creating artificial lakes, plantation land and agriculture where the santri cultivate, as well as cattle farms which are all managed by santri, the success of the Hidayatullah Islamic Boarding School in Balikpapan contributes clean water to the communities around the pesantren location. The Hidayatullah Islamic Boarding School moves its santri to organize the environment in the Gunung Tembak area. The development of Islamic boarding schools in agriculture is also an example for other pesantren. Where in the Hidayatullah Islamic Boarding School an agribusiness center was developed. On 40 hectares of critical land planted with sweet orange, lemon, zalacca, and melinjo. While the rest of the total land is 120 hectares in addition to educational land and settlements, gold teak plantations are developed. The ability of students in the field of agriculture is not only explored from self-taught abilities but also supported by training and courses